Enhanced Network Control for the Entry Process of IEEE 802.16 Mesh Networks - Macedo, Y.; Rangel, V.; Gomez, J.; Lopez-Guerrero, M.; Aquino, R. (Elektronika ir Elektrotechnika, 2012)
The IEEE 802.16-2004 standard defines a media access control (MAC) layer for a mesh network topology. In these networks, wide scale power outages can cause serious disruptions to digital services when a centralized scheduling mode is used. This results in very long service recovery times for all mesh nodes. In this paper we study the performance of the initialization process due to service disruption of IEEE 802.16-2004 mesh networks. We implemented a simulation model of the scheme using the OPNET simulation package v14. Simulation results show that the recovery times obtained with the proposed scheme can be reduced by up to 98% compared with the default scheme defined in the standard. Ill. 5, bibl. 9, tabl. 4 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1051